Contemporary public management: a new global paradigm? - Hood, Christopher (Public Policy and Administration, 1995)
This paper takes another look at the much-canvassed idea of a 'new global paradigm' emerging in contemporary public management. It argues that, linguistic usage apart, the 'globality' and monoparadigmatic character of contemporary public management change seems to be exaggerated. Three interrelated objections are advanced against the claim of an emerging new global paradigm. First, it is argued that contemporary reform ideas, particularly those advanced by Osborne and Gaebler, are culturally plural rather than homogenous. Second, it is argued that there are substantial biases towards exaggerating international similarity in public management reforms, but that the similarity weakens when we go beyond semantic packaging to examine the specific content of reform initiatives. Third, it is claimed that there are also built- in biases for overstressing the continuity of contemporary public management reforms, but that in fact there are major obstacles to the emergence of a stable new paradigm in public management. One is the underlying mutual repulsion of the multiple reform paradigms today, and the other is the frequency of self disequilibrating processes in public management reform associated with the production of unintended side-effects and reverse effects.